CLASSIFICATION AND DIAGNOSIS OF REGIONAL PROJECTS WITH USING OF FACET ANALYSIS - Savchuk, R. V. (Science and Transport Progress, 2008)
The possibilities of facet analysis for classification and diagnostics of regional innovative projects are considered in this article. The offered method allows to group projects in the aggregated classes for determination of strategy of regional management on every project..